The Eldfell Eruption, Heimaey, Iceland: A 25-Year Retrospective - Morgan, Alan (Geoscience Canada)

(untitled) (The Geological Association of Canada, 2000)
Summary The Eldfell eruption commenced on 23 January 1973 as a 1.5 km fissure crossing the island of Heimaey. Many houses close to the main vent were destroyed by pyroclasts before a flank collapse of the volcano in February allowed lava to move into the town. The Icelanders responded by spraying seawater on the lava, finally stopping the advance less than 100 m from the port quay sides. During the eruption period, which lasted until early June, more than 400 establishments were destroyed by tephra fall and lava. The residents of Vestmannaeyjar (-5300persons at the start of the eruption) were safely evacuated by trawlers and an airlift.Today (1999) the town has approximately 4800 inhabitants, and a thriving post-eruption economy.